The Effectiveness of Quadratus Lumborum Block Compared to Transversus Abdominis Plane Block in Treating Acute Pain Post Abdominal Surgery: A Systematic Review - Devina Martina Bumi; I Gusti Ngurah Mahaalit Aribawa; I Made Gede Widnyana; Tjokorda Gde Agung Senapathi (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Parameters of successful anesthesia and surgery include postoperative pain management. Abdominal surgery can cause severe pain, affect recovery, and trigger pathophysiological reactions. Quadratus lumborum block (QLB) and transversus abdominis plane (TAP) block are commonly used peripheral nerve blocks for postoperative analgesia. Methods: This systematic review aimed to compare the effectiveness of QLB and TAP block, including postoperative opioid consumption, in adults aged 18 to 65 years undergoing abdominal surgery. The review followed PRISMA guidelines and searched studies assessing QLB and TAP block for acute postoperative pain management. Result: A total of 475 records were identified, and four randomized controlled trials met the inclusion criteria for further analysis. Outcomes were synthesized descriptively using pain scores (VAS, NPIS, and NRS) and total opioid consumption. Conclusions: QLB showed more favorable primary and secondary outcomes compared with TAP block in the included studies, suggesting better postoperative analgesic effectiveness after abdominal surgery.